ANALYSIS OF CONSTRAINTS WITH ACCESS TO SECURE PROPERTY RIGHTS REGISTRATION IN AKURE, NIGERIA - Olukolajo, Michael Ayodele; Babajide, Ojo; Olukolajo, Michael Ayodele (Journal of Technology Management and Business, 2019)
A reasonable proportion of economic achievement is derivable from an active land market system that is supported with improved and formalized land right registration. However, there are still constraints with access to secure property rights registration in many states of Nigeria in contrast with the experience in developed economies. This situation inhibits a healthy real estate property market development. The paper elicited data from 150 professionals in the built environment within Akure, the capital of Ondo state, using a structured questionnaire. Factor analysis by principal components was adopted in the data analysis to classify identified twenty-one variables that constitute constraints to property rights registration in the study area. The results show that six components accounted for 77.23% of the total variance explained and a total of six factors were extracted which converged in 10 iterations. Â Time taken in achieving land title registration, the bureaucratic procedure involved, inappropriate document to work with, poor knowledge of ICT among officials and poor internet connectivity are among inhibiting factors. Â There is need to introduce modern Land Information System (LIS) and Geographic Information System (GIS) into property right registration process to make data more secure, enhance huge data storage, easy access and retrieval.